Jail inmates at midyear 2007 - Sabol, William J. (Prison and Jail Inmates at Midyear, Jail Inmates)
Presents data on numbers of jails and jail inmates at midyear 2007 and analyzes patterns of growth from 2000 through 2007. This report includes data on rated capacity of jails, percent of capacity occupied, and capacity added. It provides estimates of admissions to jails and details the volume of movement among the jail population. This Bulletin includes total numbers for jail inmates by gender, race, and Hispanic origin as well as counts of jail inmates by conviction and confinement status. Standard errors for jail estimates are only provided in the appendix tables of the electronic version of this report.